Common Narratives in Discourses on National Identity in Russia and Japan. Issue 1 (2nd January 2016) - Buntilov, Georgy
ABSTRACT: This article discusses some common narratives found in discourses on national identity in Russia and Japan, and their temporal transformations reflecting the needs of a nation as it becomes a colonial empire. National identity discourse is examined from the viewpoint of national antagonism arising from an external threat. Russian and Japanese intellectuals, with their vastly different historical and cultural heritage, have dwelled upon similar issues pertaining to modernization of the state and adoption or rejection of foreign ideas and ways of life. There are several themes in Russian and Japanese discourses on national identity that share a significant overlap, particularly themes of national uniqueness and a 'special path', deterministic worldviews, imperial cosmopolitanism/messianism and criticism of 'Western' philosophical systems and concepts. This article elucidates the shared aspects of these narratives and philosophical inquiries in Russia and Japan and puts them into a historical context.